THE EFFECT OF WORKPLACE AND STRESS MANAGEMENT ON BURNOUT IN NURSES DURING THE COVID 19 PANDEMIC (CASE STUDY AT PUSKESMAS TAROGONG, GARUT REGENCY) - Mepy Nurana; Tasya Aspiranti; Sri Suwarsi (Sean Institute, 2022)
pandemic, which experienced a significant increase in workload during the COVID-19 pandemic. Burnout is a syndrome characterized by emotional exhaustion, depersonalization, and decreased work performance, which can be caused by various factors in employee work, including high work stress and various workplace factors such as workload, rewards, job control, and others. In the era of the COVID-19 pandemic, nurses have a high risk of burnout, due to high work stress, workload, the risk of COVID-19 infection, and also have a high risk of experiencing COVID-19 transmission through close contact with patients. This study aims to analyze the effect of workplace factors and stress management on burnout among nurses at Tarogong Health Center during the COVID-19 pandemic. This research is a descriptive verification study with a census or whole sampling method, namely all nurses at Tarogong Health Center. Primary data were collected through interviews and surveys using the Maslach Burnout Inventory questionnaire, the Quick Burnout Assessment questionnaire, and the stress management questionnaire. In the workplace questionnaire for aspects of workload, control, reward, and fairness, the level is adequate, while the community and values are at a high level, meaning that there is still a need for improvement in workload management, decision making, communication, and a more transparent reward system for nurses in the workplace. Tarogong Health Center. Nurses use individual stress management methods, especially using personal relaxation techniques and discussing with partners or families to manage work stress levels. Burnout is at a moderate level marked by a degree of depersonalization and a mild decline in performance. Workplace and stress management affect the burnout of nurses at Tarogong Health Center, and the influence of workplace on burnout is greater than the effect of stress management so that an increase in workload management, decision making, and effective communication with nurses is needed, workplace interventions and stress management at the Puskesmas are also needed to reduce burnout levels, so management needs to implement stress management programs, both organizationally such as holding recreation for nurses, and need to share a fair share of workload and in active discussion with nurses.